Omega‐3 fatty acid supplementation attenuates skeletal muscle disuse atrophy during two weeks of unilateral leg immobilization in healthy young women. Issue 3 (10th January 2019) - Mcglory, Chris; Gorissen, Stefan H. M.; Kamal, Michael; Bahniwal, Ravninder; Hector, Amy J.; Baker, Steven K.; Chabowski, Adrian; Phillips, Stuart M.
ABSTRACT: Omega‐3 (n‐3) fatty acid supplementation enhances muscle protein synthesis and muscle size. Whether n‐3 fatty acid supplementation attenuates human muscle disuse atrophy is unknown. We determined the influence of n‐3 fatty acid supplementation on muscle size, mass, and integrated rates of myofibrillar protein synthesis (MyoPS) following 2 wk of muscle disuse and recovery in women. Twenty women (BMI = 23.0 ± 2.3 kg/m 2, age = 22 ± 3 yr) underwent 2 wk of unilateral limb immobilization followed by 2 wk of return to normal activity. Starting 4 wk prior to immobilization, participants consumed either 5 g/d of n‐3 fatty acid or an isoenergetic quantity of sunflower oil (control). Muscle size and mass were measured pre‐ and postimmobilization, and after recovery. Serial muscle biopsies were obtained to measure integrated (daily) MyoPS. Following immobilization, the decline in muscle volume was greater in the control group compared to the n‐3 fatty acid group (14 vs . 8%, P < 0.05) and was not different from preimmobilization at recovery in the n‐3 fatty acid group; however, it was still lower in the control group ( P < 0.05). Muscle mass was reduced in the control group only ( P < 0.05). MyoPS was higher in the n‐3 group compared with the control group at all times ( P < 0.05). We conclude that n‐3 fatty acid supplementation attenuates skeletal muscle disuse atrophy in young women, which may be mediated by higher rates of MyoPS.—McGlory, C., Gorissen, S. H. M., Kamal, M., Bahniwal, R., Hector, A. J., Baker, S. K., Chabowski, A., Phillips, S. M. Omega‐3 fatty acid supplementation attenuates skeletal muscle disuse atrophy during two weeks of unilateral leg immobilization in healthy young women. FASEB J. 33, 4586–4597 (2019). www.fasebj.org